Molecular relationship and biosynthetic potential of endophytic bacteria / Rohani Rahim and Sadia Sultan - Rahim, Rohani; Sultan, Sadia (Research Innovation Business Unit, 2014)
Bacillus sp. is known to produce numerous types of natural products such as anti fungal, anti viral, anti cancer, anti-inflammation and anti bacteria activities. The secondary metabolites products produced by bacteria are a new source for new drug development. Bacteria living inside the plant tissue without affecting the host are known as endophytic bacteria (Strobel and Daisy, 2003). In this study, Bacillus sp. was isolated from tissues of plant collected in every part of the Malaysian region. A study by local researcher stated that the tropical rainforest are diverse in biological and chemical resource and they are the reservoir for medicine and chemical lead which could be candidates for new drug (Jantan, 2004). The varieties of the tropical plants including medicinal could be the host of one or more endophytic bacteria ( Strobel and Daisy, 2003). There are no reports about endophytic bacteria isolated from tropical region plants. But, a few studies have been done for the endophytic fungi isolated from Malaysian plants and it is proved that the results are positively encouraging. The fungus isolated from medicinal plant has anti fungal, antibacterial and has the possibility of cancer drug candidates (Ramasamy, 2010). Another study by Hazalin et al., in 2009 showed that the bioactive compound produce by endophytic fungi from rainforest produce cytotoxic ability which are a good potential for anti cancer drug. Since no information is known about endophytic bacteria for Malaysia plants and perhaps this research is the good start for the bacterial endophytes study in this country. Due to the interaction of the bacteria with the plant host, some endophytes are capable of synthesizing their bioactive compounds that can be used by plants and some of them are useful in microbial metabolites research (baby and R.Mimi., 2011). In this study, the bacteria were isolated by Asian University of Medical Science and Technology (AIMST) and they were already identified by amplification of 16s rRNA sequences in polymerase chain reaction (PCR) reaction. Almost 1000 strains of the bacterial were isolated and they are from different bacteria species. But, for research only limited for Bacillus sp. collected by AIMST university and only nutrient broth were used. 16s rRNA is a useful tool for bacteria identification (Janda and Abbot, 2007) and classification of bacteria (Kwon et al., 1997 and Propocio et al., 2009), because it function as molecular clock for micro oragnism (Woese, 1987). The 16s rRNA sequences can be used to resolve the taxonomic relationships of various species, groups stemming from heterogeneity of the genus (Kwon et al., 2007). The sequence results were blast from National Centre for Biotechnology Information (NCBI) gene bank. The aim of the study is to find the molecular relationships of the bacillus species isolated from 16s rRNA sequence. The phylogenetic tree reveals that the isolates of the Bacillus sp. were similar although they were isolated from different plant species and geographical regions. Since they are similar, isolates from each species was selected for the secondary metabolites study. To express the metabolites from the bacteria, 30 ml of the nutrient broth with modification of dimethylsulfoxide (DMSO) was used. For the large scale bacteria extraction, 5 litre of nutrient broth were used. The bacteria were incubated for three days and the room temperature was 28 degree Celsius. The liquid-liquid extraction method was used to get the bacterial metabolite extracts. Only ethyl acetate and methanol were used as solvent. The crude extracts were test for antibacterial and anti fungal activity. The positive extract for antimicrobial activity will be elucidated by high performance liquid chromatography (HPLC), nuclear magnetic resonance (NMR), mass spectrometry (MS), and infra red (IR) analysis.